Physical and Mechanical Characterization of Sheep/Goat Garment Leather According to SNI 4593:2011 with Industrial Ergonomics - Wahyu Fajar Winata; Fauzi Ashari; Himawan Santoso (Industrial Innovation, 2026)
Sheep and goat garment leather is widely utilized in the apparel industry because of its softness, flexibility, lightweight characteristics, and excellent mechanical performance, making it suitable for high-quality leather garments. The quality of garment leather plays a crucial role in determining not only product durability but also wearer comfort and freedom of movement during use. This study aimed to evaluate the physical and mechanical characteristics of sheep/goat garment leather based on the requirements of SNI 4593:2011 and to discuss their implications from the perspective of industrial ergonomics. A descriptive research approach was employed using laboratory testing in accordance with SNI 4593:2011. The evaluated parameters included organoleptic properties, leather thickness, tear strength, tensile strength, elongation at break, softness, crack resistance, water absorption, finish rub fastness, and other quality characteristics specified in the standard. The experimental results were analyzed descriptively by comparing each parameter with the quality requirements established in SNI 4593:2011 to determine the conformity of the tested leather. The evaluation indicated that most of the measured physical and mechanical properties satisfied the standard requirements, demonstrating that the leather possesses adequate structural integrity and flexibility for garment applications. Nevertheless, several parameters require further optimization to achieve full compliance with the national standard and to enhance overall product quality. From an industrial ergonomics perspective, the observed mechanical properties indicate that the evaluated leather is capable of accommodating body movements while maintaining structural stability during repeated use. Appropriate flexibility, tensile strength, and softness are expected to improve range of motion, wearing comfort, and long-term durability, whereas physical characteristics related to moisture behavior may influence thermal comfort and user satisfaction. Overall, the evaluated sheep/goat garment leather demonstrated good conformity with SNI 4593:2011, suggesting its suitability for garment applications. Future improvements should focus on optimizing leather processing and finishing to enhance both material performance and ergonomic quality while preserving the favorable mechanical properties of the leather